TRANSFORMASI DAN INTEGRASI TIGA DINASTI ISLAM: KAJIAN KOMPARATIF KERAJAAN UTSMANI, DINASTI SAFAWI, DAN KEKAISARAN MUGHAL PADA ABAD KE-18 - Rosdiana, Rosdiana; Darnanengsih; Fajar Hidayat, Muhammad; Hermanto, Bambang; Rahmawati; Syukur, Syamsan (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2025)
This article examines the history of development and decline of three major Islamic empires in the 18th century, namely the Ottoman Sultanate, the Safavid Dynasty, and the Mughal Empire. These three empires were once centers of power and advanced Islamic civilization, but faced significant challenges during the early modern period (1700s-1800s) that led to a significant decline in their political, economic, and military strength. This research highlights the internal and external factors that contributed to the decline of these three empires. Through a comparative approach, the article identifies similar patterns of decline, such as the inability to adapt to changing times and resistance to reforms, although the regional context and responses to the crises varied in each empire. The long-term impact of this decline is significant for the Islamic world, including the loss of political dominance and the emergence of a colonial era that lasted until the 20th century, as well as triggering waves of renewal and modernization among Muslims. This research uses qualitative methods with an analysis of primary and secondary historical sources to provide a comprehensive picture of the political and social dynamics during this important transitional period. The findings are expected to be an important contribution to the understanding of Islamic history and a lesson for the development of future Islamic civilization.